Prophetic Business Orientation in Corporate Law Efforts to Incorporate Aspects of Divinity and Justice in Business Law: Orientasi Bisnis Profetik dalam Hukum Perusahaan: Upaya Menghadirkan Aspek Ketuhanan dan Keadilan dalam Hukum Bisnis - Sadnyini, Ida Ayu; Kurniawan, I Gede Agus (Rechtsidee, 2023)
This article explores the integration of prophetic business orientation, which combines religious and ethical values into corporate law, in the context of globalized modern economics. It employs a normative research methodology and legislative approach, analyzing the incorporation of values like transparency, ethics, and religious principles in Indonesian corporate law. The study reveals challenges related to legal uncertainty, corruption, unequal access to justice, and gender inequality in the workplace. Legal reforms and improved law enforcement are vital to promote ethical values and justice in contemporary business practices. Highlights: Ethics in Business: The study explores the concept of prophetic business orientation, emphasizing the integration of ethical and religious values into corporate law. Multi-Faceted Implementation: It highlights the diverse aspects involved in the implementation of prophetic business orientation, from transparency to environmental sustainability. Challenges and Necessity for Change: The research underscores the challenges, including legal uncertainty and corruption, and the need for legal reforms to promote ethical values and justice in modern business practices. Keywords: Prophetic Business Orientation, Corporate Law, Ethical Integration, Values in Business, Legal Reforms